2017
DOI: 10.3390/ma10111279
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Low-Concentration Mercury Removal from Aqueous Solutions by Reduced Graphene Oxide-Supported Fe3O4 Composites with the Aid of an Artificial Neural Network and Genetic Algorithm

Abstract: Reduced graphene oxide-supported Fe3O4 (Fe3O4/rGO) composites were applied in this study to remove low-concentration mercury from aqueous solutions with the aid of an artificial neural network (ANN) modeling and genetic algorithm (GA) optimization. The Fe3O4/rGO composites were prepared by the solvothermal method and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), atomic force microscopy (AFM), N2-sorption, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The acceptable range of the discrepancy between the adjusted R 2 value and the predicted R 2 value should be less than 0.20; if the numerical difference is above 2, the model is regarded as not being appropriate to fit the data [56]. In addition, the appropriate value of adequate precision should be higher than 4 [28]. In our work, the adjusted R 2 , predicted R 2 , and adequate precision were 0.9789, 0.9331, and 34.747 respectively.…”
Section: Optimal Adsorption and Interactivementioning
confidence: 99%
See 1 more Smart Citation
“…The acceptable range of the discrepancy between the adjusted R 2 value and the predicted R 2 value should be less than 0.20; if the numerical difference is above 2, the model is regarded as not being appropriate to fit the data [56]. In addition, the appropriate value of adequate precision should be higher than 4 [28]. In our work, the adjusted R 2 , predicted R 2 , and adequate precision were 0.9789, 0.9331, and 34.747 respectively.…”
Section: Optimal Adsorption and Interactivementioning
confidence: 99%
“…RSM can quantitatively evaluate interactive effects of multiple variables and effectively reduce the number of experimental variables. RSM has been applied to various wastewater treatments, such as the Fenton process, electrocoagulation, photocatalysis, membranes, and adsorption operations for optimization [24][25][26][27][28]. In addition, regarding recycled agricultural materials, rice bran, also known as miller's bran, is a common agricultural byproduct in Taiwan and can be obtained during the milling of rice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, artificial neural network (ANN) modeling appears as an alternative technique for optimization and control of MEUF process [12]. ANN networks are capable to store and process the information with distributed memory without empirical studies of the process and after learning they can make decision by commenting on similar events as literature studies showed their applications in various environmental engineering systems [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cao et al. 23 used ANN and GA to optimize low-concentration mercury removal from aqueous solutions by reduced graphene oxide-supported Fe 3 O 4 composites.…”
Section: Introductionmentioning
confidence: 99%